1990
DOI: 10.1002/jbmr.5650050608
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength as a predictor of bone mineral density in young women

Abstract: It is widely accepted that physical activity is beneficial to bone. However, the specific relationships of muscle strength to bone mineral density (BMD) are poorly understood. We examined strength and BMD in 59 women aged 18-31 years who ranged in exercise patterns from sedentary to active. Mineral density of the right proximal femur (hip) and spine (L2-4) was evaluated by dual-energy x-ray absorptiometry. BMD at the midradius was measured by single-photon absorptiometry. Dynamic strength (one repetition maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(66 citation statements)
references
References 14 publications
5
59
1
1
Order By: Relevance
“…17 Our results further support the hypothesis of a site-specific effect of muscle strength: forces arising from muscular loading and contraction not only influenced BMD but also bone quality and microarchitecture, at least in postmenopausal women. 14,17,[29][30][31][32] Quantitative ultrasound is a validated technique in acquiring information about qualitative and structural features of bone and in identifying individuals at risk for fractures. 20 To our knowledge, this is the first study evaluating the relationship between handgrip strength and qualitative features of bone, both assessed at the upper dominant limb.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our results further support the hypothesis of a site-specific effect of muscle strength: forces arising from muscular loading and contraction not only influenced BMD but also bone quality and microarchitecture, at least in postmenopausal women. 14,17,[29][30][31][32] Quantitative ultrasound is a validated technique in acquiring information about qualitative and structural features of bone and in identifying individuals at risk for fractures. 20 To our knowledge, this is the first study evaluating the relationship between handgrip strength and qualitative features of bone, both assessed at the upper dominant limb.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of adults under age 42 have suggested that physical activity is a better predictor of BMD than is knee extensor strength. (20)(21)(22) Similarly, studies of younger athletic men have revealed that, although knee extensor strength is associated with BMD at the hip, activity level predicts this relationship better than either knee extensor strength or lean body mass (LBM). (23) Alternatively, differences between our results and those of prior studies may stem from measurements used.…”
Section: Discussionmentioning
confidence: 99%
“…21 For example, knee extensor muscles have been identified as representative of lower-extremity strength because of their central role in key functional tasks, such as walking, standing from a chair, and climbing stairs. [22][23][24] Muscle strength of the limbs and trunk declines with age and is associated with an increased risk of falls, 25 hip fractures, 26 loss of bone mineral density, [27][28][29][30] and long-term survival in severe congestive heart failure, 31 functional dependence in people aged 75 years, 32 and loss of functional status in hospitalized patients. 33 Balance allows humans to be able to orient the body in space, maintain an upright posture under static and dynamic conditions, and move without falling.…”
Section: 70) Of Pearson Correlations With Criterion Measuresmentioning
confidence: 99%